Peran Kelompok Tani dalam Peningkatan Status Sosial Ekonomi Petani Padi Sawah - Iskandar Malian (IPM2KPE, 2022)
This study aims to determine the role of farmer groups in improving the socio-economic status of rice farmers before and after becoming members of farmer groups. This research method is descriptive. Determination of the number of samples using the proportional sampling method. The results showed that farmer groups played a role in improving the economic status of lowland rice farmers with a total score of 1,283 and an average of 33.76. In conclusion, the socio-economic status of farmers before becoming a member of a farmer group was low and increased to high after becoming a member of a farmer group. Keywords: Farmers Group, Rice Fields, Role, Farmers